Experimental Evaluation of a Mobile Wick Solar Still with External Condenser in Rennes, France - Sory Diarra; Sidy Mactar Sokhna; Souley Faye; Paul Byrne; Ousmane Sow (Scientific Research, New Technologies and Applications Vol. 3, 2024)
This study assesses the performance of a novel mobile wick solar still with a passive external condenser, designed and manufactured by IPFH2O. The objective of the system is to facilitate the production of potable water from non-potable water sources through the utilisation of solar energy. The system is designed for use in areas where access to drinking water remains a significant challenge. The tests were conducted over a four-day period between October and December 2021 at the University of Rennes 1, which is situated in Brittany, an area characterised by a sub-oceanic climate. The system was monitored manually in accordance with a one-hour interval schedule on the test days. The data collected included measurements of the temperatures of the components, the relative humidity, the global insolation, and the hourly production. This data was then used to calculate the system’s energy and exergy yields in order to assess the system’s performance. The data collected enables the system’s performance to be determined and compared with that of other existing solar installations. In addition, the data allows for the characterisation of the system’s operation and the proposal of technical solutions to optimise it. Distilled water production is halted completely when the sun’s rays are too weak to rotate the belt, before terminating the acquisition. The obtained data is initially processed and recorded using XFlow software. It is then converted into Excel format for further analysis.